Níveis de suplemetação de vitamina A e vitamina K para codornas de corte em crescimento - Stanquevis, Caroline Espejo (2014)
Four experiments were carried out in order to determine the levels of vitamin A andvitamin K for meat quails (Coturnix coturnix sp). In experiment I, 2000 quails from 1-14 days old were used which were distributed in a complete random experimentaldesign, a total of 8 treatments with 5 repetitions. The levels of vitamin Asupplementation were 0; 4,500; 6,000; 7,500; 9,000; 10,500; 12,000 and 13,500 UI/kgof feeding. The body weight (BW), weight gain (WG), feed conversion (FC) showed aquadratic effect (P<0.05). Feed intake (FI) and accumulated body biomass (ABB)showed linear effect. The estimating levels of vitamin A were 11,177; 11,276 and 705UI, respectively. No significant differences were observed (P>0,05) for hematocrito(HEM), relative values of heterophils (H), lymphocytes (L), heterophil / lymphocyteratio (H:L), serum enzymes aspartate aminotransferase (AST), alanine aminotransferase(ALT) and absolute liver weight (WLIVER). It was observed that this supplementationhas little effect on immunity of meat quail of 1-14 days old. It has been concluded thatthe requirement for maximum growing is 11,276 UI of vitamin A. In experiment II,1520 quails from 15 to 35 days old were used, the treatments were the same asexperiment I. The weight gain (WG) and accumulated body biomass (ABB) showed aquadratic effect (P<0.05). On the other hand, the body weight (BW) increased linearly,and the supplementation did not show statistically affected in the feed intake (FI) andfeed conversion (FC). No differences were observed (P>0.05) for hematocrit (HEM),relative values of heterophils (H), lymphocytes (L), heterophil / lymphocyte ratio (H:L),serum enzymes aspartate aminotransferase (AST) and alanine aminotransferase (ALT).It has been concluded that the requirement for maximum growing of meat quail of 15-35 days old is 7,469 UI of vitamin A. In experiment III, 2200 quails from 1-14 days oldwere used which were distributed in a complete random experimental design, total of 8treatments with 5 repetitions. The levels of vitamin K supplementation were 0; 0.7; 1.0;1.3; 1.6; 1.9; 2.2; 2.5 mg/kg of diets. There was no influence (P> 0.05) in the levels ofvitamin K supplementation on feed intake (FI), body weight (BW), weight gain (WG),biomass accumulated body (BCA) and feed conversion (FC ). There was a quadraticeffect (P <0.05) in the bone density of the femur (DOF), calcium concentration of thefemur (CAF) and bone density of the tibia (DOT). The length of the tibia (COMPT) hada linear increase (P <0.05) according to the levels of vitamin K. There was no effect (p>0.05) in the concentration of serum calcium (CAS), however, alkaline phosphatase(ALP) showed a quadratic effect (P <0.05). It was concluded that vitamin Ksupplementation did not affect the performance of meat quails from 1 to 14 days of age,otherwise the parameters related to bone quality indicate that there is a positiveinfluence of this vitamin. In experiment IV, 1520 quails from 15-35 days of age wereused, the levels of vitamin K used were the same as the ones in experiment III. Therewas no influence (P> 0.05) in the levels of vitamin K supplementation on feed intake(FI), body weight (BW), weight gain (WG), biomass accumulated body (BCA) and feedconversion (FC ). The femur diameter (DIAMF) and femur calcium concentration(CAF) and the tibial length (LENGT) and tibial calcium concentration (CAT) showed aquadratic response (P<0.05), with the highest levels found 1.33, 1.42, 1.59 and 1.42 mgof vitamin K to DIAMF, CAF, LENGT and CAT respectively. The prothrombin time,the concentration of serum calcium and alkaline phosphatase levels had also notsignificantly affected. It is concluded that levels of supplementation did not influencethe performance of meat quails, so diets based on corn and soybean meal are sufficientto meet the needs of the meat quails at this stage. The supplementation of this vitaminseems to positively influence bone quality.